Medical Cannabis for the Treatment of Migraine in Adults: A Review of the Evidence - Okusanya, Babasola O.; Lott, Breanne E.; Ehiri, John; McClelland, Jean; Rosales, Cecilia (Frontiers in Neurology, 2022)
Abstract: Background: Medical cannabis (MC) has been hypothesized as an alternative therapy for migraines, given the undesirable side effects of current migraine medications. The objective of this review was to assess the effectiveness and safety of MC for the treatment of migraine in adults. Methods: We searched PubMed, EMBASE, PsycINFO, CINAHL, and Web of Science for eligible studies in adults aged 18 years and older. Two reviewers independently screened studies for eligibility. A narrative synthesis of the included studies was conducted. Results: Twelve publications involving 1,980 participants in Italy and the United States of America were included. MC significantly reduced nausea and vomiting associated with migraine attacks after 6 months of use (P 0.0057). Also, MC reduced the number of days of migraine by 0.11 (t-test P-value =0.2039) after 30-days of MC use, and 5.8 (p<0.0001) migraine headaches reduction per month. MC was 51% more effective in reducing migraines than non-cannabis products (75.82%; SD=20.76). Similarly, MC aborted migraine headaches in 14 users (11.6%) in a study and had a reduction of migraine frequency of 40.4% compared to Amitriptyline treatment. The use of MC for migraines was associated with the occurrence of medication overuse headaches (MOH). However, adverse events were mostly mild and occurred in 43.75% of patients who used oral cannabinoid preparations. Conclusions: There is promising evidence that MC may have a beneficial effect on the onset and duration of migraine headaches in adults. However, well-designed experimental studies that assess MC's effectiveness and safety for treating migraine in adults are needed to support this hypothesis.